2023
DOI: 10.1038/s41467-023-36908-z
|View full text |Cite
|
Sign up to set email alerts
|

Beta variant COVID-19 protein booster vaccine elicits durable cross-neutralization against SARS-CoV-2 variants in non-human primates

Abstract: The rapid spread of the SARS-CoV-2 Omicron subvariants, despite the implementation of booster vaccination, has raised questions about the durability of protection conferred by current vaccines. Vaccine boosters that can induce broader and more durable immune responses against SARS-CoV-2 are urgently needed. We recently reported that our Beta-containing protein-based SARS-CoV-2 spike booster vaccine candidates with AS03 adjuvant (CoV2 preS dTM-AS03) elicited robust cross-neutralizing antibody responses at early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…However, the NVX-CoV2373 vaccine has shown promising results in adolescents; this vaccine is immunogenic and has significant GMTs [28]. The GMTs of the recombinant COVID-19 vaccines at 3 and 6 months demonstrated sustained immunogenicity and efficacy of these vaccines, highlighting their role in boosting immune responses over time and providing protection against severe COVID-19 outcomes and emerging variants [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the NVX-CoV2373 vaccine has shown promising results in adolescents; this vaccine is immunogenic and has significant GMTs [28]. The GMTs of the recombinant COVID-19 vaccines at 3 and 6 months demonstrated sustained immunogenicity and efficacy of these vaccines, highlighting their role in boosting immune responses over time and providing protection against severe COVID-19 outcomes and emerging variants [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The Sanofi Beta variant vaccine (VidPrevtyn Beta) was approved by the EU as a booster in November 2022 and remains the only COVID-19 booster vaccine using the Beta variant [ 22 ]. The researchers for VidPrevtyn Beta also argued for the use of a Beta variant-based vaccine even during the current Omicron landscape of COVID-19, citing the evidence of broad neutralization against Omicron subvariants and durability of immunity conferred by VidPrevtyn Beta in non-human primate and clinical studies [ 23 , 24 ]. AZD2816, a Beta version of AstraZeneca AZD1222, demonstrated improved neutralization against the Beta variant when AZD2816 was given as a booster dose after AZD1222 or mRNA primary series [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that soluble prefusion-stabilized Spike trimers (CoV2 preS dTM) based on the D614 sequence formulated with the AS03 adjuvant elicited a favorable safety profile and high immunogenicity against the ancestral strain in naïve adults 13 . In addition, we demonstrated that, in primed macaques, one booster dose of CoV2 preS dTM-AS03 (D614 or Beta) enhanced neutralizing antibodies (nAbs) against the ancestral virus and extended the neutralization to multiple VOC (Alpha, Beta, Gamma, Delta, and Omicron) and SARS-CoV-1 14 , 15 . Preliminary data from two clinical trials assessing CoV2 preS dTM-AS03 as a booster in COVID-19 vaccine-primed individuals confirmed these results and further suggested the superiority of the Beta monovalent vaccine formulations compared to D614 monovalent mRNA or subunit vaccines 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%